Current Trends in Tourism under COVID-19 and Future Implications - Zygmunt Kruczek; Bartłomiej Walas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The purpose of this Special Issue is to show progress regarding current research and literature on the theme of "Current Trends in Tourism under COVID-19 and Future Implications for Sustainability". In particular, this Special Issue of the peer-reviewed international journal Sustainability aspires to expand the discussion and scientific debate on a range of viewpoints, trends, approaches, cases, impacts, challenges, models, and/or frameworks relating to tourism in the time of COVID-19, as well as the possibility of implementing the principles of sustainable tourism development in the post-pandemic period. Restarting the frozen tourism economy is an opportunity to build healthy relations between various groups of tourism stakeholders, including entrepreneurs and tourists. "New tourism" also requires legal and organizational solutions in order to balance the economic relations between global and local market actors in terms of consumer protection, as well as prevent the phenomenon of overtourism. The digitization of tourism services in the areas of marketing and sales should be one of the priorities addressed by entrepreneurs and DMOs. In the literature, as well as in the media and the scientific community, the impact of the pandemic on tourism has been the most commonly discussed topic over the last two years. This Special Issue aims to explore further sustainable tourism practices.
Keywords: 330; pandemic fatigue; travelers' fear of missing out (FOMO); destination crisis marketing; post-COVID-19 tourism; vaxication intention; greatest of all trips (GOAT); international expats; theory of planned behavior; cognitive load theory; protection motivation theory; COVID-19; safety; tourism branding; health-protective behavior; Greece–Spain; customer satisfaction; P2P accommodation market; exploratory factor analysis; service quality; tourism; impact; DMO; support tools; hotel; OCC; ADR; RevPAR; revenue management; Poland; stakeholder; social capital; pandemic; collective action; community adaptation; SEM analysis; resilience; absorption; SARS-CoV-2; Tyrol; marketing; marketing mix; crisis management; COVID-19 epidemic; catering industry; restaurants; risks; stigmatized; destinations; Serbia; youth; students; tourist activity; COVID-19 pandemic; trends; perspectives; contemporary tourism; risk perceptions; travel intentions; personality traits; market segmentation; sustainable tourism; tourism industry; sustainable recovery; health crisis; tour operator; travel package; linked travel arrangements; insolvency; destination management organizations; tourism technology; content analysis; thematic analysis; smart tourism destination; smart city; sustainable development; systematic literature review (SLR); research agenda; package holiday; tourist decision-making; tourist behavior; tourism sustainability; Masai Mara; policy interventions; Kenya; bibliometric study; VOS viewer; R bibliometrix; government subsidies; perceived quality; perceived behavioral control; predicted risks; travel intention; behavioral intention; online digital exhibition; competence; meetings industry; management; post-COVID; museums in a pandemic